From Struggle to Success: The Feynman Techniques' Revolutionary Impact on Slow Learners - Adeoye, Moses Adeleke (Universitas Pendidikan Ganesha, 2023)
Feynman Techniques have proven to be a game-changer in the field of education. The Feynman Techniques, developed by physicist Richard Feynman, provide a unique and effective approach to learning complex subjects. By breaking down information into simple terms and teaching it to others, slow learners can enhance their understanding and retention of material. This study aims to analyze revolutionary impact of the Feynman Techniques on slow learners in their journey from struggle to success. This research uses the Systematic Literature Review (SLR) method. The data collection stages in this research were carried out in search for and identify relevant data sources, carry out literature selection, and extract relevant data. This research uses thematic analysis methods to identify patterns, trends and main findings in the literature reviewed. This study found the principles behind the Feynman Techniques and highlights their practical application in educational settings. It also presents case studies and testimonials from slow learners who have experienced significant improvements in their academic performance and self-confidence after implementing these techniques. The findings suggest that the Feynman Techniques have the potential to revolutionize the way slow learners approach learning and achieve success.